One click Jeff Bezos and the rise of Amazon.com - Brandt, Richard L (New York Portfolio Penguin, 2011)
"An insightful look at how Amazon really works and how its founder and CEO makes it happen. Amazon's business model is deceptively simple: make online shopping so easy and convenient that customers won't think twice. It can almost be summed up by the button on every page: Buy now with one click. Why has Amazon been so successful? Much of it has to do with Jeff Bezos, the CEO and founder, whose unique combination of character traits and business strategy have driven Amazon to the top of the online retail world. Originally a computer nerd rather than a businessman, he had the vision to capitalize on the untapped online marketplace for bookselling and continues to discover new market opportunities, from groceries to auto parts. He's a calculating machine, high energy, passionate, highly aggressive, and out to radically transform retail. Through numerous interviews with Amazon employees, competitors, and observers, Richard Brandt has deciphered how Bezos thinks, what drives his actions, and how he makes decisions. Anyone in business can learn a lot from the example of Amazon's ongoing evolution. "--
One click is not enough -- Portrait of the entrepreneur as a young man -- Jeff gets a job -- Jeff discovers the internet -- Three nerds and an accountant -- How to build a better bookstore -- Growing pains -- Money to burn through -- Growing up -- Who you calling a bookstore? -- The crash -- Bezos bets big on the Kindle -- Is Amazon killing the bookstore? -- A cool guy with a funny laugh -- But what kind of manager is he? -- Head in the clouds -- Step by step, courageously.
Includes bibliographical references and index.
Keywords: Bezos, Jeffrey; Amazon.com (Firm) -- History; Booksellers and bookselling -- United States -- Biography; Businessmen -- United States -- Biography; Internet bookstores -- United States -- History; Electronic commerce -- United States -- History